Cone beam tomography evaluation of lingual cortical mandibular defect diagnosed as Stafne bone cavity - Allan ABUABARA; Flares Baratto-Filho; Giuseppe Valduga CRUZ; Liliane GUERINO; Allan GIOVANINI (Revista Sul-Brasileira de Odontologia, 2010)
Introduction: Mandibular lingual bone depressions are considered to be developmental anomalies known as Stafne bone cavity. The purpose of the present report is to describe the characteristics of classic Stafne bone cavity in molar region evaluated by cone beam computed tomography (CBCT). Case report: A male patient, 27 years old, was submitted to CBCT to evaluation of the relation between the right lower third molar roots and mandibular canal and the unilateral cystic image found in the panoramic radiographic below the mandibular canal in the right molar area. It was used a gray scale of 12 bits and voxel of 0.2 mm. The CBCT showed fine images of the Stafne bone cavity. In the present case, periodic clinical and radiological controls were the therapeutic option. In atypical cases or in doubtful diagnosis, surgical intervention and anatomopathological examination may be indicated. Conclusion: Although the diagnosis of a Stafne bone cavity can often be established with plain radiographs, confirmatory tests are sometimes required. In these situations, the diagnosis can be confirmed with CBCT.